2004
DOI: 10.1182/blood-2004-03-1224
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for Notch1 distinguishes 2 phases of definitive hematopoiesis during development

Abstract: Notch1 is known to play a critical role in regulating fates in numerous cell types, including those of the hematopoietic lineage. Multiple defects exhibited by Notch1-deficient embryos confound the determination of Notch1 function in early hematopoietic development in vivo. To overcome this limitation, we examined the developmental potential of Notch1–/– embryonic stem (ES) cells by in vitro differentiation and by in vivo chimera analysis. Notch1 was found to affect primitive erythropoiesis differentially duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
206
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(225 citation statements)
references
References 74 publications
18
206
1
Order By: Relevance
“…In turn, notch activation in the hematopoietic stem cells was increased, leading to an increase in the stem cell numbers (Calvi et al, 2003). This notch dependence of hematopoietic stem cells is also seen in development as the notch 1-null (Kumano et al, 2003), notch 1-chimeric (Hadland et al, 2004), and RBPjkappa (a transcription factor required for notch activity)-null mice (Robert-Moreno et al, 2005) all show abnormal hematopoietic stem cell development. In muscle stem cells (satellite cells), activated notch increases proliferation while inhibition of notch signaling by its antagonist, numb, results in commitment of progenitor cells to myoblast cell fate (Conboy and Rando, 2002).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 98%
See 1 more Smart Citation
“…In turn, notch activation in the hematopoietic stem cells was increased, leading to an increase in the stem cell numbers (Calvi et al, 2003). This notch dependence of hematopoietic stem cells is also seen in development as the notch 1-null (Kumano et al, 2003), notch 1-chimeric (Hadland et al, 2004), and RBPjkappa (a transcription factor required for notch activity)-null mice (Robert-Moreno et al, 2005) all show abnormal hematopoietic stem cell development. In muscle stem cells (satellite cells), activated notch increases proliferation while inhibition of notch signaling by its antagonist, numb, results in commitment of progenitor cells to myoblast cell fate (Conboy and Rando, 2002).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 98%
“…Soluble factors such as BMPs (Xie and Spradling, 1998;Kobielak et al, 2003;Zhang et al, 2003;Andl et al, 2004;He et al, 2004;Yamashita et al, 2005), FGFs (Kashiwakura and Takahashi, 2005), Shh (Madison et al, 2005;Crosnier et al, 2006), and Wnts (Gat et al, 1998;Korinek et al, 1998;Huelsken et al, 2001;Niemann et al, 2002;Reya et al, 2003;Willert et al, 2003) are present within the niche and can originate from support cells, stem cells themselves, or differentiated cell. Cell-to-cell contact-mediated signaling is also present in adult niches in the form of connexins (Juneja et al, 1999;Plum et al, 2000), ephrins/eph (Batlle et al, 2002;Holmberg et al, 2006) and Notch (Harada et al, 1999;Lowell et al, 2000;Conboy and Rando, 2002;Calvi et al, 2003;Conboy et al, 2003;Kumano et al, 2003;Tummers and Thesleff, 2003;Hadland et al, 2004;Fre et al, 2005;Robert-Moreno et al, 2005;van Es et al, 2005;Spradling, 2006, 2007;Song et al, 2007). These signaling mechanisms may occur between stem cells, between support cells and stem cells, and between stem cells and differentiating cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gene deletion studies in both zebra fish and mice have demonstrated a potential role for Notch signaling in hematopoietic and endothelial development. [4][5][6]8,9,25,39 In addition, both Notch1 and Jagged1 are implicated in the induction of definitive over primitive hematopoiesis. 4,16,25 Notch1-deficient mouse embryonic stem cells contribute to primitive yolk-sac hematopoiesis in chimeric mice but are incapable of adult blood development, 4 whereas Jagged1 is required for the establishment of definitive mouse hematopoietic precursors.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]8,9,25,39 In addition, both Notch1 and Jagged1 are implicated in the induction of definitive over primitive hematopoiesis. 4,16,25 Notch1-deficient mouse embryonic stem cells contribute to primitive yolk-sac hematopoiesis in chimeric mice but are incapable of adult blood development, 4 whereas Jagged1 is required for the establishment of definitive mouse hematopoietic precursors. 25 Controlling lineage specification from hPSCs remains a primary goal of regenerative medicine research; however, few reports have used exogenous factors to control cell fate commitment to one lineage over another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation